The importance of early life in childhood obesity and related diseases: a report from the 2014 Gravida Strategic Summit. (13th October 2014) - Macaulay, E. C.; Donovan, E. L.; Leask, M. P.; Bloomfield, F. H.; Vickers, M. H.; Dearden, P. K.; Baker, P. N.
<x content-type="archive" xml:space="preserve">Abstract</x> Obesity and its related non-communicable diseases (NCDs), such as type 2 diabetes, heart disease and cancer, impose huge burdens on society, particularly the healthcare system. Until recently, public health and policy were primarily focused on secondary prevention and treatment of NCDs. However, epidemiological and experimental evidence indicates that early-life exposures influence the risk of childhood obesity and related diseases later in life, and has now focused attention on the health of both mother and child. During pregnancy and the early neonatal period, individuals respond to their environment by establishing anatomical, physiological and biochemical trajectories that shape their future health. This period of developmental plasticity provides an early window of opportunity to mitigate the environmental insults that may increase an individual's sensitivity to, or risk of, developing obesity or related diseases later in life. Although much investigation has already occurred in the area of Developmental Origins of Health and Disease research, the science itself is still in its infancy. It remains for researchers to tackle the important outstanding questions and translate their knowledge into workable solutions for the public good. The challenge, however, is to decide which areas to focus on. With these opportunities and challenges in mind, the 2014 Gravida Summit convened to examine how its early-life research program can determine which areas of research into mechanisms, biomarkers and interventions could contribute to the international research strategy to fight childhood obesity and its related diseases.